Scleredema diabeticorum - A case report - O.I. Ezejiofor; O. Onayemi; O.A. Olasode; R.T. Ikem; A.A. Komolafe; I.F. Ezejiofor (Wolters Kluwer Medknow Publications, 2015)
Scleredema, a medical problem first described by Buschke in 1902, is a rare scleromatosis of unknown aetiology, which is characterized by wooden, nonpitting induration of the skin. This skin disorder first affects the neck and face and may symmetrically spread to the shoulders, trunk, arms, and legs. We report a case of a 65 year-old hypertensive and diabetic male who presented with marked thickening of the upper back with obvious peau d'orange changes. Association with other complications of diabetes is not certain and treatment is difficult, though improvement is possible with optimal glycaemic control. Scleredema diabeticorum is rare and is a cause of significant morbidity in diabetes.